Using bootstrap method in analyzing the factors affecting study result of HCMUTE student - Nguyen , Hong Nhung (Journal of Technical Education Science, 2016)
Bootstrap is a modern statistical method and has been used widely because it doesn’t require emperical distribution function as classcical methods do. This article will focus on demonstration of bootstrap method and the use of this approach to analyze the factors which affected on the study results of students of HCMC University of Technology and Education. Then conclusion shall be stated basing on data analysis process.